Bibliometric analysis of international publication trends on social media and terrorism by using the Scopus database - Yumitro, Gonda; Febriani, Rizki; Roziqin, Ali; Indraningtyas, Anisa (Frontiers in Communication, 2023)
Social Media and Terrorism are topics often studied together and have become the focus of many researchers in recent years. This study aims to evaluate trends in international publications on social media and terrorism using the Scopus database through bibliometric analysis from 2009 to 2022. Data visualization and analysis were conducted using Microsoft Excel and VOSviewer. The results showed that the trend of international publications on social media and terrorism reached a peak in 2018, with 103 publications covering topics such as social media, terrorism, Twitter, terrorist attacks, and various issues related to terrorist activities and other forms of social media. The United States was the most common country of publication and had the highest number of affiliated authors. The authors with the most published documents were Tsikrika t. and Vrochidis s, while the majority of published documents were articles in the field of social sciences. This research contributes to the novelty of previous studies on social media and terrorism.